Efficacy Test of Matoa Leaf Plant Extract as an Anticonvul-sant in Mice With Acute Seizure Model - Haryanto Haryanto; Jannatin Aliyah; Lisa Aulya Nur; Rania Rania; Febby Vebiola; Cantika Nayla Zahra Febriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Indonesia is recognized as one of the world’s richest countries in terms of biodiversity, including a wide variety of traditional medicinal plants. One of the lesser-known yet promising local species is matoa (Pometia pinnata J.R. Forst & G. Forst), whose leaves have been traditionally used by local communities to treat various ailments, including diarrhea and seizures. This study aims to investigate the pharmacological effects of matoa leaf extract, with a particular focus on its anticonvulsant activity, while also reviewing its potential chemical constituents as a basis for herbal medicine development. The research was conducted using a combination of literature review and experimental testing on mice (Mus musculus) induced with strychnine to trigger seizures. Key observed parameters included seizure onset time and survival duration (dead time) following the administration of either synthetic drugs or matoa leaf extract. The results demonstrated that the matoa leaf extract exhibited significant anticonvulsant effects, as indicated by prolonged seizure onset and increased survival time in test animals. These pharmacological effects are presumed to be related to the presence of active compounds such as flavonoids, tannins, and alkaloids, which may contribute to the stabilization of the central nervous system. Compared to conventional synthetic anticonvulsants, matoa leaf extract may offer a safer, plant-based alternative with potentially fewer side effects. The findings of this study provide valuable scientific evidence supporting the potential of Pometia pinnata leaves in the development of Indonesian herbal phytopharmaceuticals. Furthermore, they highlight the importance of further research, including preclinical and clinical trials, to validate efficacy, determine optimal dosages, and ensure safety for human use.